Powder Production via Atomisation and Subsequent Laser Powder Bed Fusion Processing of Fe+316L Steel Hybrid Alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Krüger, Jan Tobias; Hengsbach, Florian; Kircheis, Alexander; Zhao, Weiyu; Fischer-Bühner, Jörg; Schaper, Mirko (Powders)
The current investigation shows the feasibility of 316L steel powder production via three different argon gas atomisation routes (closed coupled atomisation, free fall atomisation with and without hot gas), along with subsequent sample production by laser powder bed fusion (PBF-LB). Here, a mixture of pure Fe and atomised 316L steel powder is used for PBF-LB to induce a chemical composition gradient in the microstructure. Optical microscopy and μ-CT investigations proved that the samples processed by PBF-LB exhibit very little porosity. Combined EBSD-EDS measurements show the chemical composition gradient leading to the formation of a local fcc-structure. Upon heat treatment (1100 °C, 14 h), the chemical composition is homogeneous throughout the microstructure. A moderate decrease (1060 to 985 MPa) in the sample’s ultimate tensile strength (UTS) is observed after heat treatment. However, the total elongation of the as-built and heat-treated samples remains the same (≈22%). Similarly, a slight decrease in the hardness from 341 to 307 HV1 is observed upon heat treatment.

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

An Experimental and Computational Modeling Study on Additively Manufactured Micro‐Architectured Ti–24Nb–4Zr–8Sn Hollow‐Strut Lattice Structures - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Andreiev, Anatolii; Schaper, Mirko; Hoyer, Kay-Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Modiﬁcation of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)

Modification of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science